2020
DOI: 10.1177/0267659120982226
|View full text |Cite
|
Sign up to set email alerts
|

The short-term prognostic value of serum platelet to hemoglobin in patients with type A acute aortic dissection

Abstract: Purpose: Type A acute aortic dissection (AAD) is an uncommon catastrophic cardiovascular disease with high pre-hospital mortality rate without timely and effectively treated. The aim of this study was to assess the value of serum platelet to hemoglobin (PHR) in predicting in-hospital mortality in type A AAD patients. Methods: A total of 183 type A AAD patients were included in this retrospective investigation from January 2017 to December 2019. Admission blood routine parameters were gathered and PHR was compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Bedel et al [ 16 ] reported a correlation between high PLR (> 195.8) and increased in-hospital mortality in patients with AAAD. However, Yang et al [ 17 ] found that a high preoperative PLR (≥ 150) was associated with a low incidence of postoperative adverse events. Contrastingly, Sbarouni et al found no association between the PLR and mortality [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bedel et al [ 16 ] reported a correlation between high PLR (> 195.8) and increased in-hospital mortality in patients with AAAD. However, Yang et al [ 17 ] found that a high preoperative PLR (≥ 150) was associated with a low incidence of postoperative adverse events. Contrastingly, Sbarouni et al found no association between the PLR and mortality [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bedel et al [ 16 ] reported that a high PLR at admission was associated with increased in-hospital mortality in patients with AAAD. However, Yang et al [ 17 ] suggested that a high preoperative PLR in patients with AAAD is correlated with a better prognosis. In addition, a study demonstrated that the PLR could be used for the differential diagnoses of similar diseases, but its usefulness in prognosis assessment should be further investigated [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, patients with a CPB duration of ≥257.5 min were more likely to suffer severe ALI after surgery than those with a CBP duration of <257.5. Decreased hemoglobin levels have been associated with poor prognosis in a variety of cardiovascular diseases 15–17 . However, interestingly, hemoglobin levels of ≤139.5 g/L were determined to be associated with a reduction in postoperative severe ALI risk in this study.…”
Section: Discussionmentioning
confidence: 51%
“…Decreased hemoglobin levels have been associated with poor prognosis in a variety of cardiovascular diseases. [15][16][17] However, interestingly, hemoglobin levels of ≤139.5 g/L were determined to be associated with a reduction in postoperative severe ALI risk in this study.…”
Section: Discussionmentioning
confidence: 54%
“…3,4) Our previous study also indicated that platelet to hemoglobin could be acted as an independent factor to predict the short outcome for TAAAD patients. 5) However, indicators that are precise, simple, practical, and easily available are still lacking, especially for patients who have undergone surgical treatment.…”
mentioning
confidence: 99%